RETALIASI ISLAMOPHOBIA DI PRANCIS DALAM PRINSIP MAQASHID SYARI’AH DHARURIYYAH - Fajrina, Siti; Surwandono, Surwandono (JPP (Jurnal Politik Profetik), 2021)
This article describes the Islamophobia in France and the boycott of French products by Islamic countries due to the French Government's statement regarding the caricature of the Prophet Muhammad. With a focus on the concept of Maqashid Syari'ah Dharuriyyah, this paper will analyze how the Dharuriyyah principle can protect beliefs and whether this boycott has a significant impact in France. The data from this paper were obtained through the Mendeley library and processed using the analytical description method with VosViewer. The result of this paper is that the boycott carried out by Muslims with the maintenance of religion under the context of Dharuriyyah succeeded in realizing the French economy with the decline in the stock market in France.